(untitled) (Nexus International Journal of Science and Education, 2024)
This study investigates the significant relationship between multicultural instruction and the English learning attitudes of senior high school students. The research involved a sample of 150 senior high school students from Cluster 4 Public Secondary Schools in Davao City for the quantitative phase, and 10 students were selected for in-depth interviews (IDIs) and focus group discussions (FGDs) in the qualitative phase. Employing a mixed-method research design with an explanatory sequential approach, the data collected were analyzed using mean and Pearson's r correlation analysis. The findings indicated that multicultural instruction was rated as moderately extensive, while the English learning attitude of senior high school students was rated as extensive. Correlation analysis revealed a significant relationship between multicultural instruction and the English learning attitudes of the students. Thematic analysis corroborated the quantitative findings, highlighting increased motivation, alignment with technology skills, and self-directed learning as key factors confirming the significant relationship between multicultural instruction and students' English learning attitudes. The study's findings advocate for further dissemination through publication in reputable research journals.